Effect of using cognitive tools on students’ thinking skills in model generation activities - Derya Akyol, Polat Şendurur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The purpose of this study is to investigate the effect of using cognitive tools on 8th grade students’ thinking skills through model construction processes with model eliciting activities. The study was conducted with 46 secondary school-8th grade students. Six different modeling activities existing in literature were used as data collection tools. Students in experimental group solved the modeling problems with the help of spreadsheets, which was used as the cognitive tool, while control group solved the same problems with traditional methods. Conducted mathematical operations and letters written by students during problem-solving processes were taken into consideration. They were analyzed under following titles that are based on Complex Thinking Model (CTM): “Critical Thinking”, “Creative Thinking” and “Complex Thinking”, and thus CTM scores were calculated accordingly. The results of the analyses indicated that students identified six different aspects of the cognitive tools, which were “facilitation, reduced effort for computation, time saving, and concentration on the problem, accurate information, and easy access to information”. The obtained CTM scores showed that the cognitive tool utilized in the current study highly contributed to the Critical Thinking skills, while it had slight contributions to the Creative Thinking skills.